Development of Sustainable Curriculum Management System with Server-Driven Go and Next.js - Adi Fitrianto; Farel Artanto Kangadi; Sestri Novia Rizki; Verra Budhi Lestari; Eko Amri Jaya (Brilliance: Research of Artificial Intelligence, 2025)
Curriculum management is a crucial aspect of educational administration, encompassing the planning, organization, and continuous updating of course data and curriculum structures. In many educational institutions, including those in Jakarta, this process still encounters challenges such as inefficiency, data duplication, inconsistent information flow, and high system maintenance overhead. These issues often result in delays, administrative burdens, and reduced productivity. This research aims to develop a sustainable curriculum management system by leveraging Go technology on the backend and Next.js on the frontend, adopting a server-driven approach to minimize processing loads on client devices, improve resource efficiency, and ensure faster data delivery. The system development method employs an iterative approach with the integration of ten supporting technologies, including server-side data fetching, Backend for Frontend (BFF), OpenAPI 3 with code generation, Redis caching, tag-based revalidation, Server-Sent Events (SSE), component-based UI, image optimization, and asynchronous job queues for heavy tasks. The system integrates course and curriculum name management into a single, responsive, secure, and easily extensible platform. Implementation results demonstrate that the approach can reduce maintenance complexity, improve data consistency, and significantly enhance application response time under varying loads. Furthermore, the system supports sustainable software engineering principles, enabling scalability and adaptability to future needs. Consequently, it offers an effective, long-term solution for curriculum management, contributing to operational efficiency and the overall quality of academic administration in educational institutions across Jakarta.